Perancangan Sistem Informasi Manajemen Aset Berbasis Web pada Divisi Teknologi Informasi PAM JAYA - syafril, royani; Wahyudin, Wahyudin (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
The Information Technology Division of PAM JAYA faces challenges in asset management due to the continued use of manual, spreadsheet-based methods, which lead to tracking difficulties, data loss risks, and delays in reporting. This study aims to design and develop SIMASPAM (Sistem Informasi Manajemen Aset PAM JAYA), a web-based asset management information system, to improve efficiency, accuracy, and integration in asset administration. The system was developed using the Agile methodology, which supports iterative development and flexibility in responding to changing user needs. It is built with the CodeIgniter 3 framework using the Model View-Controller (MVC) architecture, integrated with the SB Admin 2 template, and uses MySQL as the database. Key features include asset recording and monitoring, maintenance and disposal management, asset tracking via QR Codes, report generation in PDF format, and automated email notifications for maintenance reminders. The system was tested using the Blackbox method, and results showed that all functionalities performed as expected. SIMASPAM was implemented locally using XAMPP and is designed to be further developed, including the potential for integration with other systems. This study demonstrates that SIMASPAM has the potential to improve work efficiency and data accuracy in asset management for the Information Technology Division of PAM JAYA.